Phenetic taxonomy approach: Identifying relationship of local gelodok fish in East Java - Khusna , Ulia Asmaul; Fadzilah , Heni Nur; Raihan , M.; Pramesti , Hervanny Putri; Salfiah, Elok Najwa; Rahayu , Dwi Anggorowati (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2024)
Various natural and human factors have fragmented the populations of Mudskippers, which will disrupt their existence in the wild population, especially their mangrove habitat in East Java. Classification of relationships is identified as a first step in efforts to conserve fish outside their natural habitat. The relationship determination is based on phenetic characteristics supported by morphometric, meristic, and morphological characters. The purpose of this study was to identify the relationship of gelodok fish based on phenetic characters. The method used in the phenetic analysis is UPGMA (Unweighted pair-group using arithmetic) using NTSYSpc 2.01 software. There are four types of fish can be found in those areas, which are: Periophthalmodon schlosseri, Periophthalmus argentilineatus, Boleophthalmus pectinirostris, and Boleophthalmus boddarti. Based on the dendrogram of morphological analysis results, apomorphy A and apomorphy B were obtained, namely the Periophthalmodon schlosseri clade and the Periophthalmus argentilineatus clade with a similarity level of 90.322% and the Boleophthalmus pectinirostris clade and the Boleophthalmus boddarti clade with a similarity level of 78.494%. The relationship between the species Periophthalmodon schlosseri and Periophthalmus argentilineatus is very close with a value of 90%. While the species Boleophthalmus pectinirostris and Boleophthalmus boddarti have a closely relationship with a value of 78%. It is recommended to develop targeted conservation strategies to protect the most unique and vulnerable populations.